The Leukodystrophies - Gordon, Hannah B.; Letsou, Anthea; Bonkowsky, Joshua L. (Seminars in Neurology, 2014)
Leukodystrophies are a group of genetically determined disorders that affect development or maintenance of central nervous system myelin. Leukodystrophies have a reported incidence of 1 in 7500 live births, but fewer than half of patients receive a specific diagnosis. In this review, the authors discuss types of leukodystrophies: their prevalence, clinical presentation, symptoms, and diagnosis, as well as current and future treatments. Diagnosis is based on a combination of history, exam, radiological, and laboratory findings, including genetic testing. Leukodystrophies can present at any age from infancy to adulthood, with variability in disease progression and clinical presentation, ranging from developmental delay to seizures to spasticity. Although there are few cures, there are significant opportunities for care and improvements in patient well-being. Their high prevalence, combined with rapid advances in imaging, genetics, and potential treatments, makes an understanding of the leukodystrophies necessary for care providers in genetics and neurology.
Keywords: leukodystrophy; myelin; adrenoleukodystrophy; metachromatic leukodystrophy; bone marrow transplantation; enzymatic replacement therapy; hematopoietic stem cell transplantation